2010
DOI: 10.1007/s11259-010-9436-8
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant avian leukosis viruses of subgroup J isolated from field infected commercial layer chickens with hemangioma and myeloid leukosis possess an insertion in the E element

Abstract: BackgroundFive isolates (JS09GY2, JS09GY3, JS09GY4, JS09GY5, and JS09GY6) of avian leukosis virus subgroup J (ALV-J) were isolated from six infected commercial layer flocks displaying both hemangioma and myeloid leukosis (ML), which shared the same parental line, in China in 2009.ResultsAll six of the commercial layer chickens examined showed hemangiomas on their body surface or feet. Some developed hemangiomas in their internal organs, causing hepatorrhexis and blood loss. Histopathologically different stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…In addition, sequence changes in the U3 region have been implicated in both the level of viral transcription and the oncogenic potential of ALVs (Cullen et al, 1985;Ryden et al, 1993). A comparison of the U3 sequences in ALV-J broiler strains and layer isolates indicated that the U3 region of ALV-J layer isolates has evolved rapidly (Hue et al, 2006;Gao et al, 2012;Wu et al, 2010). The results of this study suggested that the stronger enhancer activity of the U3 region that was substituted from RSV resulted in a faster replication rate of the recombinant ALV-J strain.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, sequence changes in the U3 region have been implicated in both the level of viral transcription and the oncogenic potential of ALVs (Cullen et al, 1985;Ryden et al, 1993). A comparison of the U3 sequences in ALV-J broiler strains and layer isolates indicated that the U3 region of ALV-J layer isolates has evolved rapidly (Hue et al, 2006;Gao et al, 2012;Wu et al, 2010). The results of this study suggested that the stronger enhancer activity of the U3 region that was substituted from RSV resulted in a faster replication rate of the recombinant ALV-J strain.…”
Section: Discussionmentioning
confidence: 68%
“…Recombination has been observed between exogenous viruses, between exogenous and endogenous viruses, and between exogenous virus and nonhomologous cellular genes, e.g. a strain of ALV-J with a primer-binding site leader sequence that originated from other retroviruses (Wu et al, 2010), a naturally occurring recombinant ALV-B strain with a subgroup J-like longterminal repeat (Gingerich et al, 2002;Lupiani et al, 2006), a recombinant that was composed of most of the ALV-J genome and part of the corresponding env sequence of ALV-E , and a recombinant ALV with ALV-A gp85 and the ALV-E LTR, which originated from contaminated Marek's disease vaccines (Barbosa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although an intact E element was not a critical requirement for the ALV-J induction of tumors, the presence of the E element could be associated with a higher frequency of tumors in susceptible chickens (8). The ALV-Js isolated from layer flocks induced a high incidence of hemangioma in China (6,36). However, previous studies indicated that the dominant tumor induced by ALV-J infection in meat-type chickens was a myelocytoma (ML) (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, field cases of ALV-J infection and tumors in commercial layer chickens emerged in 2004 (37). ALV-J has been found to induce various tumors and cause significant economic losses in parent and commercial layer flocks in recent years, especially from 2008 to 2010 (6,14,18,36). Many field cases of ALV-J infection and tumors occurred in 15-to 29-week-old egg-type chickens in several provinces.…”
mentioning
confidence: 99%
See 1 more Smart Citation